Peran Serikat Pekerja dalam Menyelesaikan Peselisihan Hubungan Industrial di Kota Tangerang - Utama, Zahera Mega; Uniariny, Uniariny; Nur, Auliah Ichwan; Sulandri, Sulandri (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study explores the strategic role of labor unions in resolving industrial relations disputes in Tangerang City, one of the major industrial centers in Banten Province, Indonesia. In the dynamic reality of modern labor relations, tensions often arise between workers who seek fairness and protection and employers who prioritize efficiency and profit. Using a qualitative case study approach, this research seeks to gain an in-depth understanding of how labor unions help balance power in the workplace. Data were collected through in-depth interviews, field observations, and document analysis involving union representatives, government officials, company management, and workers engaged in labor conflicts. The findings reveal that labor unions serve as advocates, watchdogs, enforcers of agreements, mediators in negotiations, educators for members, and facilitators of social dialogue. These roles have proven effective in resolving conflicts peacefully, often preventing escalation into formal legal processes. The study emphasizes that the presence of active and empowered labor unions is essential for building fair, healthy, and sustainable industrial relations especially in labor-dense industrial regions such as Tangerang City.